Enhancing Islamic Religious Education: Development and Validation of Canva-Assisted E-Module for Halal Consumption and Haram Avoidance at SMPN 7 Palopo City - Firdaus, Megawati; Baderiah, Baderiah; Ihsan, Muhammad (Educational Journal of Learning Technology, 2023)
This thesis is entitled The Development of an Islamic Religious Education Learning e-module assisted by Canva on consuming halal food and drinks and avoiding haram at SMPN 7 Palopo City. The research aims to analyse students' needs for e-module development, the validity of e-modules, and the practicality of e-modules. This research uses R&D (Research and Development) research with the ADDIE development model, which consists of five development stages: analysis, design, development, implementation and evaluation. The results of this research indicate that the Islamic religious education learning e-module was developed for the needs of students. The validation results of the Islamic religious education learning e-module, namely media expert validation, obtained a percentage of 79.16% with valid criteria, and material expert validation results obtained a rate of 85% with very good criteria. For the e-module practicality test obtained from educators, the percentage was 96.5% in the very practical category, and the e-module practicality test obtained from students obtained a percentage of 89.5% in the very practical category. It was concluded that the Canva-based Islamic religious education learning e-module on consuming halal food and drinks and avoiding haram ones is suitable for the learning process.